CREB, Synapses and Memory Disorders: Past Progress and Future Challenges - Josselyn, Sheena A.; Nguyen, Peter V. (Current Drug Targets-CNS & Neurological Disorders, 2005)
In neurons, appropriate long-term adaptive responses to changes in the environment require the conversion of extracellular stimuli into discrete intracellular signals. Many of these signals involve the regulation of gene expression. The cAMP responsive element binding protein (CREB) is a nuclear transcription factor that modulates transcription of genes containing cAMP responsive elements (CRE sites) in their promoters. CREB is a key part of many intracellular signaling events that critically regulate many neural functions. Numerous studies on invertebrates and vertebrates demonstrate that CREB is critical for long-term memory. Here, we review the key features of CREB-dependent transcription and critically evaluate the data examining the roles of CREB in different forms of plasticity, including longterm memory in mammals. Because learning and memory have been linked to specific types of synaptic plasticity in several species, we also review studies on the role of CREB in long-term facilitation in Aplysia and in hippocampal longterm potentiation (LTP). Several human cognitive disorders have been linked to alterations of CREB-regulated gene expression. Therefore, we explore the possibility of targeting CREB function in developing novel treatment strategies. Finally, we highlight areas of research on CREB that are ripe for further advancement.
Keywords: cyclic-amp